Sob a espada de Dâmocles: a construção profissional do praça da Polícia Militar do Ceará e as metamorfoses do trabalho - Lima, Ítalo Emanuel Pinheiro de (2023)
The initial decades of the 21st century confirmed a significant movement towards the restructuring of society. The changes occurred in the State, at work and in the subjects who experience these processes show phenomena of interest to the Social Psychology of Work. The plurality of workers within the complex class-that-lives-from-work makes us perceive movements that intertwine in their individual and collective dimensions. A group of workers within this context. Police work has been discussed by different fields of knowledge in recent years, whether for questions about the increase in violence, whether for the ways in which it has been responding to the demands resulting from this situation or for the representativeness of its work in society. From fields such as education, history and sociology to Psychology, this collective of workers, particularly for us, the members of the military police, express phenomena that have yet to be investigated, and one of them seems to transversalize the entire context outlined here: professionalization. Such condition, so required towards workers, seems to be a fertile field for the production of senses and meanings involved in the construction of workers' subjectivity. Thus, understanding how, amid the metamorphoses of work, the worker constitutes himself, produces his daily life, transforming reality and being transformed by it, experiencing the professional condition, becomes a relevant theme from a social, academic point of view, and, as a worker and researcher, from a personal point of view. This thesis started from the initial question of how military police officers in the state of Ceará experience the various metamorphoses of/at work from the process of professionalization of police activity in recent years. To achieve this objective, we made initial contact with professionals in the area, all of them with more than 10 years of experience in the security force from Ceará state. The selection used initial indications by the “snowball” strategy, soliciting indications from future informants. Data were collected directly from informants in the model of individual interviews, of work trajectories, in person or mediated by video call, recorded and transcribed, and the collected information were submitted to analysis from a qualitative bias supported by Sociological Discourse Analysis (SDA). Each trajectory was worked on in its uniqueness, highlighting points in which the participant emphasized relevant clippings for their professionalization process, in which themes such as precarious work, excessive strain, devaluation of work, work intensification and lack of care were explicit. A transversal content was also identified in the speeches, which linked the individual experience to the political context of the collective of workers. Professionalizing appears not only as a qualification or training process, but as a process of modeling craft and gender. It is at this moment that beinga professional is linked to a condition of expressing health, a strategy to see oneself alive within the activity. More than answering our initial question, this thesis opens gaps, possibilities for future paths and all of them necessarily imply the presence and participation of workers.